Contexts of Ensuring Ecological Stability in The Process of Global Political Threats (International Journal of Scientific Trends, 2026)
This article provides ideas about the current global threats, their forms of formation, scale and impact on humanity. In the last twenty years, the struggles and conflicts for water, called “Blue Gold”, which is considered the greatest threat to humanity, are analyzed. Possible forecasts are given about the scale and estimated damage of this problem for developing countries.